ASSESSMENT OF ACIDIFICATION IMPACTS IN THE MEDITERRANEAN SEA: FROM META-ANALYSIS TO ECOSYSTEM SERVICES VALUATION - ZUNINO, SERENA (Università degli Studi di Trieste, 2018)
Since the industrial revolution and the extensive use of fossil fuels, oceans worldwide have absorbed about a quarter of the anthropogenic CO2 released by human activities. The continued uptake of CO2 from the atmosphere alters the carbonate chemistry of the oceans and increases the concentration of hydrogen ions, thereby reducing pH, a phenomenon called ocean acidification (OA). Ocean acidification is expected to cause significant changes in the marine environment over the coming century leading to relevant effects on the biological, biogeochemical and ecological components of the marine environment, as well as potentially relevant – but still not fully quantified – consequences on related socio-economic dimensions. The aim of the work is to analyse the effects of ocean acidification in the Mediterranean Sea from organisms responses to the ecosystems functioning levels. In particular, this work focuses on two important habitats, the coralligenous formations and Posidonia oceanica meadows, and investigates the provisioning and cultural services provided by these habitats. Among the relevant services in the context of OA, we analysed provisioning services using fisheries landing indicators and cultural services using values related to the scuba-diving tourism. These assessments are applied to the Italian seas and highlight the potential degradation cost caused by seawater acidification. Chapter 1 presents a quantitative synthesis (meta-analysis) of the OA studies performed in the Mediterranean Sea within a realistic range of pH alteration in agreement with the expected CO2 emission trends forecasted by the Intergovernmental Panel on Climate change for the “business as usual” emission scenario for the year 2100. The results of the meta-analysis highlight the existence of direct effects but also suggest the instauration of indirect effects that could trigger habitats modifications. In Chapter 2, the results of the meta-analysis present in Chapter 1 and additional literature information are used to build conceptual ...